Social justice : distributive principles and beyond - Dube, M. P.
Justice is one of the primary qualities of a good political order. With rising disparities of income, wealth, and access to opportunity in many liberal societies, justice is now a concern for everyone. Each member of society wants and expects one's fair share of wealth, income, political power, social recognition, education, and other resources and opportunities. The question this book broaches is the specific standard that should be employed in assessing what one deserves. To utilitarian theorists, a socially just allocation is ultimately an allocation that produces the greatest sum of happiness. The most ambitious attempt to answer these questions was provided by John Rawls. Rawls's view is that justice demands 'maximum equal liberty, ' and a distribution of economic benefits which makes the least favoured person as well off as possible. But Hayek and Nozick challenge John Rawls's arguments, saying that distributive principles are incompatible with individual liberty. In the traditional distributional approach, the sole emphasis on distribution without an examination of the underlying causes of the mal-distributions was not acceptable to several contemporary political theorists such as, Iris Young, Nancy Frazer, Axel Honneth and Charles Taylor. Amartya Sen and Martha Nussbaum who have expanded the conception of justice beyond Rawls (distributive justice) by an advancing capability approach. Today, even environmental and ecological justice have become very important themes of discussion for social and political theorists. The idea of social justice implies more than just granting political and legal equality by the state. This book pursues this line of inquiry by providing students, scholars, and policy makers with an extensive review of research on social justice in India. [Subject: Political Theory, Social Theory, India Studies, South Asian Studies